2019
DOI: 10.18203/2320-1770.ijrcog20192416
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function in abnormal uterine bleeding

Abstract: Background: AUB is any abnormal uterine bleeding in the absence of any palpable pelvic pathology and demonstrable extra genital causes. AUB is responsible for 10% of gynaecological complaints. Thyroid hormone is very important to affect the menstrual pattern. The objective of this study was to evaluate thyroid function test in women with AUB and to assess the menstrual pattern in women with thyroid dysfunction. Methods: The present study was conducted in the Department of Obstetrics and Gynecology, Laxmi Naras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“…Similarly in study by Kundoor R et al 10 majority of thyroid disorder was subclinical hypothyroid (15%), followed by hypothyroid 10% and hyperthyroid 2.5%. In study by Sudha HC et al 8 euthyroid constituted 62% patients, hypothyroid 12%, Subclinical hypothyroid in 16% and hyperthyroid in 2% patients.…”
Section: Discussionmentioning
confidence: 65%
“…Similarly in study by Kundoor R et al 10 majority of thyroid disorder was subclinical hypothyroid (15%), followed by hypothyroid 10% and hyperthyroid 2.5%. In study by Sudha HC et al 8 euthyroid constituted 62% patients, hypothyroid 12%, Subclinical hypothyroid in 16% and hyperthyroid in 2% patients.…”
Section: Discussionmentioning
confidence: 65%
“…According to Kolli et al, in patients with subclinical and overt hypothyroidism, menorrhagia was found to be 55% prevalent, followed by polymenorrhagia, acyclical bleeding, polymenorrhea, oligomenorrhea, and metrorrhagia [ 18 ]. In another study conducted among women of reproductive age, subclinical hypothyroidism was found in about 15 seemingly normal individuals with AUB (15%) [ 19 ]. Pujari et al conducted a study in a tertiary hospital in India on patients with subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…The cases of thyroid dys-function are on rise worldwide [4] . In India also the same is observed for which there may be multiple causes like family history or lifestyle modifications or excess of stress [7] . Earlier studies reported that there was more cases of hypothyroidism and sub clinical hypothyroidism in the women of reproductive age [8] .…”
Section: Discussionmentioning
confidence: 64%